2018
DOI: 10.1039/c8nj04228d
|View full text |Cite
|
Sign up to set email alerts
|

Hydrous nickel sulphide nanoparticle decorated 3D graphene foam electrodes for enhanced supercapacitive performance of an asymmetric device

Abstract: Hydrous nickel sulphide is successfully synthesized on graphene foam (Ni9S8/GF) using a facile chemical bath deposition (CBD) method for supercapacitor application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…Further, growth of cobalt phosphate thin films can take place by adsorption of colloidal particles from the solution at the nucleation centers on the SS substrate. Typically, at high temperature (at 365 K), decomposition of urea gradually forms CO 2 and NH 4 + ions in solution, and released NH 4 + acts as a complexing agent in the reaction bath. , After decomposition of urea, NH 4 + and Co 2+ ions get complexed as [Co­(NH 3 )] 2+ . The amine complex avoids rapid nucleation and controls the reaction rate by gradually releasing Co 2+ ions.…”
Section: Resultsmentioning
confidence: 99%
“…Further, growth of cobalt phosphate thin films can take place by adsorption of colloidal particles from the solution at the nucleation centers on the SS substrate. Typically, at high temperature (at 365 K), decomposition of urea gradually forms CO 2 and NH 4 + ions in solution, and released NH 4 + acts as a complexing agent in the reaction bath. , After decomposition of urea, NH 4 + and Co 2+ ions get complexed as [Co­(NH 3 )] 2+ . The amine complex avoids rapid nucleation and controls the reaction rate by gradually releasing Co 2+ ions.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the mutual supporting roles of both rGO and as-synthesized oxides promote the higher specific capacitance of the present oxide-rGO composite materials for exhibiting high-performance supercapacitor performance. 29,31,32,34 Furthermore, the GCD plots of each composite material do not exhibit any significant iR drop in both the electrolyte mediums, which clearly demonstrate that a very negligible internal resistance can be generated at the interface of electrodes and electrolytes. 18,19,[21][22][23][24][25]32,34,63,64 Such a lower internal resistance can prevent extra heat generation during the charge/discharge processes and also restrict the loss of energy which is another important requisite for the energy-storage device applications.…”
Section: ■ Experimental Sectionsmentioning
confidence: 77%
“…48 The capacitance could be higher as a result of the smaller size and the larger surface area resulting from the layered, two-dimensional morphology. 49 It has been observed that with the increase in current density, the specific capacitance decreases, as shown in Fig. 6(b).…”
Section: (C) Therementioning
confidence: 83%